O PCB / Edgard Carone - Carone, Edgard (Corpo e alma do Brasil ; 60-62)
Lanzamiento con motivo del 60 aniversario del P.C.B. | Contiene : Vol. I (1922-1943). - IX, 350 p. Vol. II (1943-1964). - VIII, 325 p. Vol III (1964-1982). - VIII, 400 p.